Forensic Applications of Markers Present on the X Chromosome - Husam Al-Tabra, Reem; Abdul Lateef Mahdi, Asia; Mahdi Al–Zubaidi, Mohammed; Khalid Ibrahim Al-Sammaraie, Halah; A. Jawad, Asmaa; Ameen Abd el_Jabbar, Ban; Nabil Hameed, Sura (Al-Nahrain Journal of Science, 2024)
The X chromosome is one of the two sex chromosomes found in humans and other mammals. It plays a crucial role in determining an individual's sex and contains genetic information that can be useful in forensic and human identity testing. Unlike autosomal DNA, which is inherited from both parents, the X chromosome is inherited differently in males and females, making it useful in certain types of analyses. In forensic investigations, the X chromosome can be used to determine the sex of an individual, which can be useful in identifying potential suspects or victims. Additionally, X chromosome analysis can be used to link evidence samples to a particular individual or to exclude individuals as potential contributors of the evidence. This can be particularly useful in cases where the evidence sample is a mixture of DNA from multiple individuals. In human identity testing, the X chromosome can be used in situations where other types of DNA analysis are not possible or inconclusive. For example, in cases where a potential parent is unavailable for testing, analysis of the X chromosome can be used to determine if a child is likely to be their biological offspring. Similarly, in cases where traditional autosomal DNA analysis is inconclusive, X chromosome analysis can be used to provide additional information about the biological relationship between individuals. However, there are some limitations to the use of X chromosome analysis in forensic and human identity testing. One limitation is that it is not as informative as autosomal DNA analysis, as it contains less genetic information. Additionally, the inheritance patterns of the X chromosome can be complex, particularly in cases where there are multiple generations involved. Therefore, X chromosome analysis should be interpreted in conjunction with other types of DNA analysis and other forms of evidence to ensure accurate and reliable results. Overall, the use of X chromosome analysis in forensic and human identity testing can provide important information in certain situations, particularly where traditional DNA analysis is not possible or inconclusive. As such, it is an important tool in the fields of forensic science and human identification.